Estudos sobre o esporte: proposição de uma unidade didática para alunos de ensino médio - Ernesto José Dutra (2020)
This study deals with a new look at the teaching of sport in school, a look at sport as a phenomenon in itself, its historicity, its social, cultural, and economic relevance. Due to the magnitude of the sports phenomenon and its importance in society, this study proves to be relevant, as it presents a tool, Teaching Unit, possible for a different pedagogical treatment with the teaching of sport at school. The methodology is based on the precepts of qualitative research, specifically in action research and teaching research. The sample consisted of 18 students of both genders, aged 15 to 18 years. The contents of the Teaching Unit on the teaching of the sport were developed, and at the end of each meeting, a focus group was held in order to verify the students' impressions about the class, the feelings, and the knowledge about the conceptual knowledge of the class theme. During the content analysis (BARDIN, 2016) of the students' speeches, it was noticed a good acceptance of the students about the Teaching Unit, who also reported having fulfilled their final objective, to present a new way of teaching sport at school. We conclude that there is no right way to work with teaching sports at school. We intend to present this study in order to aggregate fundamental skills and competences in teaching for physical education at school, providing for the domain of practice reflections and references on pedagogical practice in the conditions of real teaching practice.